The Influence of Affiliate Content Type and Source Credibility on Perceived Trust and Purchase Intention on TikTok Shop: A Study of Air Freshener Products - Kamila Rahandini (Green Publisher Indonesia, 2025)
This study investigates how different types of affiliate content and the source credibility of creators influence consumer trust and purchase intention on TikTok Shop, using Stella air freshener as a case product. Grounded in the Elaboration Likelihood Model (ELM) and Source Credibility Theory (SCT), the study examines how content types (tutorial, testimonial, promotional) and source credibility affect perceived trust, which in turn mediates their effect on purchase intention. A quantitative method was employed, collecting responses from 186 TikTok users exposed to air freshener affiliate content. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that tutorial and testimonial formats significantly enhance perceived trust and indirectly influence purchase intention, while promotional content does not. Source credibility also significantly influences trust but has only a marginal direct effect on purchase. The study concludes that trust-centered content is essential in affiliate strategies for sensory products and provides practical guidance for brands on content planning and creator briefing.